FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA KEKAMBUHAN PADA PENDERITA GANGGUAN JIWA DI WILAYAH KERJA PUSKESMAS SUNGAI DAREH KABUPATEN DHARMASRAYA - Yuli Permata Sari; Vivi Nofita Sapitri; Yaslina Yaslina (LPPM UNIVERSITAS PERINTIS INDONESIA, 2018)
Mental disorders are a group of psychotic disorders, with a basic disorder of personality, a distinctive distortion of thought processes. Based on WHO data in 2015 the prevalence of mental disorders is 465 million in the world. Civil Registry Agency (BPS) 2015, the prevalence of people with mental disorders Indonesia reached 15.3% of the 259.9 million inhabitants of Indonesia. Based on data from Health Research Association (RISKESDAS) West Sumatera Province in 2015 mentions the prevalence of mental disorders 1.9 per mile. In the working area of ​​Puskesmas Sungai Dareh Dharmasraya district mental disorders increase annually where during the year 2015 is about 47 people, and in 2016 about 49 people. The purpose of this study is to determine